A proposal for the models and measures of search and rescue on inland waterways - Vidan, Pero; Kasum, Josip; Jolić, Natalija (Transport, 2010)
Search and rescue on inland waterways are considered to be insufficiently developed. The methods of search and rescue have been developed only for sea waterways. Despite the possibilities of comparison, the specific characteristics of inland waterways are the reason why it is seriously considered to develop proposals for search and rescue models on inland waterways. The authors of this paper suggest a search and rescue model for rivers, lakes and channels regarding configuration and the current safety conditions on inland waterways. The model allows a successful quest for reduced search time. In addition, the model predicts the performance of the search.First published online: 27 Oct 2010